Varenicline treatment for methamphetamine dependence: A randomized, double-blind phase II clinical trial. (1st August 2018) - Briones, Marisa; Shoptaw, Steven; Cook, Ryan; Worley, Matthew; Swanson, Aimee-Noelle; Moody, David E.; Fang, Wenfang B.; Tsuang, John; Furst, Benjamin; Heinzerling, Keith
Highlights: Varenicline is proposed as a treatment for methamphetamine dependence. A randomized clinical trial (RCT) of varenicline (1 mg BID) or placebo conditions for 9 weeks was conducted. Varenicline did not reduce methamphetamine use in this cohort. Abstract: Background: Previous studies have suggested that varenicline, an α4β2 nicotinic receptor partial agonist, and α7 nicotinic receptor full agonist, may be effective for the treatment of methamphetamine (MA) dependence due to dopaminergic effects, relief of glutamatergic and cognitive dysfunction, and activation of nicotinic cholinergic systems. This study aimed to determine if varenicline (1 mg BID) resulted in reduced methamphetamine use compared to placebo among treatment-seeking MA-dependent volunteers. Methods: Treatment-seeking MA-dependent volunteers were randomized to varenicline 1 mg twice daily (n = 27) or placebo (n = 25) and cognitive behavioral therapy for 9 weeks. The primary outcomes were the proportion of participants achieving end-of-treatment-abstinence (EOTA, MA-negative urine specimens during weeks 8 and 9) and the treatment effectiveness score (TES, number of MA-negative urine specimens) for varenicline versus placebo. Results: There was no significant difference in EOTA between varenicline (15%, 4/27) and placebo (20%, 5/25; p = 0.9). There was some suggestion that urinary confirmed medication compliance corresponded with EOTA in the varenicline condition, though it did not reach statistical significance, OR = 1.57 for a 100 ng/ml increase in urine varenicline, p = 0.10, 95% CI (0.99, 3.02). There was no significant difference in mean TES in the varenicline condition (8.6) compared to the placebo condition (8.1), and treatment condition was not a statistically significant predictor of TES, IRR = 1.01, p = 0.9, 95% CI (0.39, 2.70). Conclusions: The results of this study indicate that 1 mg varenicline BID was not an effective treatment for MA dependence among treatment-seeking MA-dependent volunteers.